Single-Dish Radio Polarimetry in the F-GAMMA Program with the Effelsberg 100-m Radio Telescope - Beuchert Tobias; Kadler Matthias; Wilms Jörn; Angelakis Emmanouil; Fuhrmann Lars; Myserlis Ioannis; Nestoras Ioannis; Kraus Alex; Bach Uwe; Ros Eduardo; Grossberger Christoph; Schulz Robert (EPJ Web of Conferences, 2013)
Studying the variability of polarized AGN jet emission in the radio band is crucial for understanding the dynamics of moving shocks as well as the structure of the underlying magnetic field. The 100-m Effelsberg Telescope is a high-quality instrument for studying the long-term variability of both total and polarized intensity as well as the electric-vector position angle. Since 2007, the F-GAMMA program has been monitoring the linear polarized emission of roughly 60 blazars at 11 frequencies between 2.7 and 43 GHz. Here, we describe the calibration of the polarimetric data at 5 and 10 GHz and the resulting F-GAMMA full-Stokes light curves for the exemplary case of the radio galaxy 3C 111.